Transarterial embolization ablation of hepatocellular carcinoma with a lipiodol-ethanol mixture - Gu, Yang-Kui (Baishideng Publishing Group Co., Limited, 2010)
AIM: To determine the safety and effectiveness of transarterial embolization ablation (TEA) of hepatocellular carcinoma (HCC) with a lipiodol-ethanol mixture. METHODS: Between January 1 and December 31, 2009, 15 patients with HCC (13 men/two women, aged 38-75 years) accepted TEA treatment and were enrolled in this study, including five newly diagnosed patients and 10 with refractory disease. Two months after TEA, angiography and contrast computed tomography (CT) were performed, and responses were assessed using a modified version of Response Evaluation Criteria in Solid Tumors (RECIST version 1.1). The follow-up period was to June 30, 2010. RESULTS: Every new case was treated once. Angiography was performed immediately after TEA, and showed that the tumor-feeding vessels were completely embolized and that lipiodol was densely deposited inside tumors. Two months after treatment, contrast CT showed no enhanced lesions. Alpha fetoprotein levels returned to normal in four patients and markedly decreased in another. mean ± SD survival after treatment was 10.8 ± 4.5 mo. All five patients survived during the follow-up period. Ten patients with refractory disease were treated a total of 14 times. Angiography immediately after TEA showed that blood flow to the tumors was obviously decreased in all cases, and contrast CT showed obvious depositions of lipiodol. Two months after treatment, the tumors had shrunk (6/10) or were stable (3/10). One had progressed after 2 mo and died of tumor rupture 3 mo after TEA. mean ± SD survival after treatment was 8.6 ± 4.3 mo; two patients survived during the follow-up period. Adverse effects included reversible hepatic decompensation, upper abdominal pain, and fever. CONCLUSION: TEA is an effective therapy for patients with HCC and might be more effective than transcather arterial chemoembolization for treating refractory disease.